Fluctuations in produced charged particle multiplicities in relativistic nuclear collisions for simulated events. (October 2019) - Ahmad, M. Ayaz; Baker, Jalal Hasan; Rasool, Mir Hashim; Ahmad, Shafiq; Dobra, R.; Pasculescu, D.; Telles, Charles Roberto
Abstract: The event-by-event (E-by-E) fluctuations have been studied for relativistic heavy ion collisions and compared by theoretical prediction of available event generators. The multiplicity fluctuations are sensitive to QCD phase transition and to the presence of critical point in the QCD phase diagram. These fluctuations also provide baselines for other event-by-event (E-by-E) measurements. In the present article, a modest approach attempt has been made for a logical study of event-by-event (E-by-E) charge fluctuations in the relativistic nuclear collisions of proton-proton (p-p) and nucleus-nucleus (A-A) interactions. Finally, simulations by Monte Carlo Generators (MCGs) have been done and findings were found within good agreements with other works.